Inflammation Driven Vascular Dysregulation in Chronic Rhinosinusitis - Khurana, Nitish (Int Forum Allergy Rhinol, 2020)
BACKGROUND: Altered neovascularity is typically observed in chronic inflammatory diseases with overlapping pathophysiology to that observed in chronic rhinosinusitis (CRS). However, the characterization of these inflammatory-induced vascular mediated changes in CRS is limited. Understanding the underlying vascular changes in CRS will allow for strategic design and development of new drug delivery technologies that exploit vascular permeability for increased extravasation into the target sinonasal tissues. METHODS: Patients with CRS with nasal polyps (CRSwNP) and without (CRSsNP), in addition to non-CRS controls were enrolled into a prospective observational study. The extent of angiogenesis in tissue was characterized using immunohistochemical and multiplex gene expression analyses. Vascular permeability, interendothelial junction structures, and endothelial barrier morphology were evaluated using transmission electron microscopy. RESULTS: Sinonasal vascularity was significantly increased in CRSsNP and CRSwNP (p<0.05) compared to controls, as assessed by enumerating the platelet endothelial cell adhesion molecule (PECAM-1)-positive blood vessels. Pro-angiogenic gene expression, including PECAM1 and platelet activating factor receptor, was significantly elevated in patients with CRSwNP compared to controls (p<0.05). The fenestration sizes between endothelial cells (17–280 nm) were larger in CRSwNP compared to CRSsNP (10–33 nm5) and controls (4–12 nm). Global thinning of the endothelial cell lining was observed in patients with CRS compared to controls. CONCLUSION: Significant increases in vascularity, pro-angiogenic gene and protein expression, and blood vessel morphogenesis were observed in patients with CRS compared to controls. Further, fenestration sizes between interendothelial junction structures were larger in CRS compared to controls, suggesting inflammation-driven vascular dysregulation in CRS pathology.